Ali je raztezanje PNF učinkovitejše v primerjavi z drugimi tehnikami raztezanja? - Kranjc, Sara (Šport (Ljubljana), 2024)
Stretching is an important part of the training method, as it contributes to improving flexibility and reducing the risk of injury. The aim of this article was to review existing research on the acute and chronic effects of PNF stretching compared to static and dynamic stretching, focusing primarily on their impact on flexibility, muscle stiffness, and performance in athletic tasks. Various studies have compared the effects of these stretching techniques. The review showed that all forms of stretching are effective in acutely increasing range of motion, with no statistically significant differences between PNF and static stretching, although in some studies, both have proven to be more effective in improving range of motion compared to dynamic stretching. Despite PNF stretching often being presented as more effective, the results indicate that its effects are similar to those of static stretching. One of the key findings is that the impact of stretching depends on several factors, including gender, the specificity of muscle groups, and the duration and intensity of the stretching. Therefore, despite numerous studies, there are still many uncertainties, highlighting the need for further research, particularly in understanding the neuromuscular mechanisms that affect stretching outcomes and the long-term effects of these techniques on reducing muscle stiffness and improving athletic performance.
Keywords: flexibility; gibljivost; mišična togost; muscle stiffness; obseg giba; performance; range of motion; raztezanje; sport; stretching; šport; zmogljivost